Design, Analysis and Optimization of a Hybrid Microgrid System Using HOMER Software: Eskişehir Osmangazi University Example - Çetinbaş, İpek; Tamyürek, Bünyamin; Demirtaş, Mehmet (International Journal of Renewable Energy Development, 2019)
This study presents design, performance analysis, and optimization of a hybrid microgrid for the hospital complex located on Eskişehir Osmangazi University (ESOGU) campus using Hybrid Optimization of Multiple Energy Resources (HOMER) software. Solar energy potential of the campus and the real electricity consumption of the hospital collected over one-year period were used in the design of the microgrid. The optimization takes into account the overall performance and the economic feasibility of the microgrid system over its lifetime. The designed microgrid consisting of photovoltaic (PV) modules, diesel generators, batteries, converters, and loads is configured as a grid-connected hybrid system. In order to optimize the system, PV module failures, increase in demand, increase in fuel cost of diesel generators, and mains interruptions are defined as performance variables and realistically modelled in the HOMER simulation. Later, both the individual and the combined effects of these variables on the performance of the microgrid was investigated via simulation using five operating scenarios. The objective was to obtain reliable data from the microgrid design that reflects the realistic operation of microgrid over its 25-years of service time. Simulation results have shown that the economic feasibility and the performance of the microgrid are greatly affected by these factors. For example, in a worst case scenario where all variables are acting together, net present cost increases to 40.44%, cost of energy increases to 21.92%, and operating cost rises to 53.91%. Moreover, the results show a reduction up to 33.30% in the portion of energy that is directly transferred from renewable sources to the load. The simulation results were then used to optimize the design of the microgrid system for the best overall performance. In conclusion, it was demonstrated that the proposed hybrid microgrid system supplies the energy demand of the hospital, lowers the cost of electricity consumption, provides a reasonable payback time, and the best of all, it contributes to the clean campus concept.©2019. CBIORE-IJRED. All rights reserved   Article History: Received May 16th 2018; Received in revised form October 18th 2018; Accepted December 16th 2018; Available onlineHow to Cite This Article: Çetinbaş, I., Tamyürek, B., and Demirtaş, M. (2019) Design, Analysis, and Optimization of a Hybrid Microgrid System Using HOMER Software: Eskişehir Osmangazi University Example. Int. Journal of Renewable Energy Development, 8(1), 65-79.https://doi.org/10.14710/ijred.8.1.65-79